Minimally invasive simple prostatectomy in the era of laser enucleation for high-volume prostates: A systematic review and meta-analysis - Abi Chebel, Josselin (Arab J Urol, 2020)
OBJECTIVE: To perform a systematic review and meta-analysis of available prospective and retrospective studies comparing the minimally invasive (laparoscopic or robot-assisted) simple prostatectomy (MISP) and laser enucleation of the prostate for treating male lower urinary tract symptoms in high-volume prostates, as laser enucleation of the prostate is the new trend for treating high-volume prostates (>80 mL) but many urologists now prefer MISP. METHODS: A systematic search was done using the Medical Literature Analysis and Retrieval System Online (MEDLINE) and Cochrane databases in June 2019, with research terms including: ‘laser’, ‘laparoscopy’, ‘enucleation’, ‘BPH’, ‘simple prostatectomy’, ‘Millins’, and ‘adenomectomy’. The meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. RESULTS: Of 38 screened articles, six were analysed and a total of 975 men were included. The average operative time, length of stay and catheterisation time were significantly shorter in the laser enucleation group (P = 0.006, P < 0.001 and P < 0.001, respectively). The amount of prostatic tissue removed during surgery was comparable between both the laser enucleation and MISP groups (P = 0.39). The International Prostate Symptom Score, prostate-specific antigen level, maximum urinary flow rate and post-void residual urine volume were also comparable at 3 months. Finally, similar transfusion rates and Clavien–Dindo complication rates were observed (P = 0.08 and P = 0.41, respectively). CONCLUSION: This systematic review of the literature and meta-analysis provide a further demonstration of the safety and effectiveness of both laser enucleation and MISP. While laser enucleation had a shorter catheterisation time and hospital stay than MISP, the latter still had unique and specific indications. Abbreviations: ELEP: eraser laser enucleation of the prostate; HoLEP: holmium laser enucleation of the prostate; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; PVR: post-void residual urine volume; Q(max): maximum urinary flow rate; (L)(MI)(RA)SP: (laparoscopic) (minimally-invasive) (robot-assisted) simple prostatectomy